Angas-Sura Etymologies IX - Takács, Gábor (Lingua Posnaniensis, 2022)
The paper is a new contribution to revealing the afro-asiatic heritage in the lexicon of the angas-Sura group of Chadic languages by means of interbranch comparison using a.o. the ancient egypto-Semitic evidence.